(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
In this work we investigate the coating of 3D-printed polymer structures with a robotic atmospheric pressure plasma jet with (3-aminopropyl)tri-methoxysilane. In particular, we investigated how deeply the coatings penetrate into the porous polymer structures and whether the nucleophilic groups are preserved. The influence of other process parameters (duty cycle, temperature, angle of the plasma jet to the substrate surface) is also discussed.